Inherited Cancer Syndromes Current Clinical Management - Ellis, C. Neal.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
The advances in our understanding of genetics has exploded since the publication of the first edition of Inherited Cancer Syndromes. We$1 (Bve moved from an incomplete understanding of the human genome to the availability of over-the-counter DNA analysis kits. There is simply too much complicated, high-level science for a busy clinician to meaningfully absorb without a filter. Inherited Cancer Syndromes is designed to bridge that gap. With this new edition, the clinical content has been expanded and clarified in order to be more tightly focused on the real-world implications of emerging therapies. The chapter authors are among the leading experts in these topics. Naturally, this book is not meant to be an exhaustive (3z(Bhow to(3y (Btextbook or procedure-heavy monograph, but a clinically relevant overview of this dynamic and difficult aspect of cancer patient care. (3z (BThe chapters on syndromes are divided by type of cancer, and each includes discussions of risk assessment, indications for genetic testing, interpretation of test results, and integration into clinical management of risk estimates and results of genetic testing. The chapter on breast cancer also provides an insightful discussion of surrogate end-point markers. Each syndrome of susceptibility to polyposis and nonpolyposis colon cancer is described, with algorithms as to when genetic testing is indicated. Guidelines for prevention and management follow. $1! = (BThis book provides the knowledge base needed for most physicians to incorporate the principles of inherited susceptibility to cancer and genetic testing properly into their practices. It is highly recommended, since many physicians and health care workers have not been trained in this area, which has become an established part of clinical medicine.(3y (BBook Review, New England Journal of Medicine Volume 351:2137-2138 November 11, 2004 Number 20s
Keywords: Medicine; Oncology; Human genetics; Cancer -- Surgery; Surgery; Medicine & Public Health; General Surgery; Oncology; Surgical Oncology; Human Genetics; Cancer Research